Medan Police Public Relations Strategy in Reducing Traffic Accidents Through Social Media Content - Athallah Rafif Syuja; Nursapia Harahap (PERSPEKTIF, 2026)
Previous studies on police public relations have primarily focused on law enforcement, conventional public communication, and traffic safety campaigns, while limited attention has been given to how police institutions strategically employ social media as a digital public relations tool to promote traffic safety awareness. This study addresses this gap by analyzing the public relations strategy of the Medan Police in reducing traffic accidents through social media content. A descriptive qualitative approach was employed using in-depth interviews, observations, and documentation. The study involved public relations personnel of the Medan Police and six members of the Medan community representing students and public workers as research informants. Data were analyzed through data reduction, data display, and conclusion drawing with source triangulation to ensure credibility. The findings reveal that the Medan Police implements a segmented digital public relations strategy by tailoring educational content to the characteristics of different audiences, with Instagram targeting younger users and Facebook targeting adults. The communication strategy combines educational flyers, visual content, and short videos to enhance message accessibility and public engagement while strengthening awareness of traffic safety. The novelty of this study lies in demonstrating how audience segmentation and platform-specific content strategies are integrated into police digital public relations practices for traffic safety education. This study contributes to the development of digital public communication literature by providing empirical evidence on strategic social media utilization within public sector organizations to support community-oriented traffic safety campaigns.